2007
DOI: 10.1038/sj.eye.6702930
|View full text |Cite
|
Sign up to set email alerts
|

Screening for ocular surface disease in the intensive care unit

Abstract: Purpose Ventilated patients in the intensive care unit (ICU) often develop exposure keratopathy. This predisposes to the development of bacterial keratitis, which in ICU is often bilateral, with a high risk of perforation. As regular examinations of all ventilated patients by ophthalmologists would be impractical, the purpose of this study was to assess whether ICU staff can screen reliably for keratopathy. Methods A prospective study was performed in a general adult ICU. Twice each week, two junior ICU doctor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 22 publications
1
69
1
10
Order By: Relevance
“…McHugh et al demonstrated in a study of ICU patients that poor or inadequate eyelid closure was associated with 70% incidence of EK when compared to 29% incidence among patients able to fully close their eyelids [4]. The use of pharmacologic-induced paralysis or heavy sedation may inhibit this important natural mechanism of eye protection [6].…”
Section: Exposure Keratopathy: Pathophysiology Diagnosis Symptoms mentioning
confidence: 99%
See 3 more Smart Citations
“…McHugh et al demonstrated in a study of ICU patients that poor or inadequate eyelid closure was associated with 70% incidence of EK when compared to 29% incidence among patients able to fully close their eyelids [4]. The use of pharmacologic-induced paralysis or heavy sedation may inhibit this important natural mechanism of eye protection [6].…”
Section: Exposure Keratopathy: Pathophysiology Diagnosis Symptoms mentioning
confidence: 99%
“…ICU doctors had 77.8% sensitivity and 96.7% specificity in detecting EK, with all "missed" cases having erosions involving <5% of the corneal surface. The authors concluded that using regular eye checks, ICU staff should be able to adequately diagnose EK and facilitate ocular therapy [4].…”
Section: Exposure Keratopathy: Preventive Strategies and Patient Safementioning
confidence: 99%
See 2 more Smart Citations
“…13,17 It was observed, so, that the muscular relaxation promoted by the action of neuromuscular blocking causes the decrease of the tonus of the eyelid which favors the incomplete closure. 6,16,18,20 The lowering of the low score evidenced awareness level on the Glasgow Coma Scale is identified in several studies as a risk factor that contributes significantly to the development of the injury, since patients with neurological deficits have their natural reflexes and protection mechanisms committed. The respiratory tract infection associated with prolonged use of mechanical ventilation settles frequently in these patients so that bacterial translocation respiratory tract eyewear during tracheal aspiration without eye protection patient was identified as an aggravating factor, because in many cases there are accidental spills of tracheal aspirates during the procedure.…”
Section: Relaxants or Muscle Blockersmentioning
confidence: 99%